Pelatihan Budidaya Cabai di Polybag sebagai Adaptasi Pertanian di Daerah Rawan Banjir - Rahmad Rafli; Ditahardiyani, Prima; Isnaniah; Ahmad Fauji; Ahmad Sauri; Ragil Dianor (Jurnal Inovasi Pengabdian Masyarakat, 2026)
Sungai Bangkal Village, Sungai Tabuk District, Banjar Regency, is a flood-prone area where seasonal flooding frequently disrupts agricultural activities, leading to decreased household income and food security. This community service program aimed to improve community knowledge and skills in utilizing home yards through chili cultivation training using polybag media as an adaptive farming strategy in flooded areas. The methods applied included socialization, technical training on chili cultivation, field practice assistance, and program evaluation using a participatory approach. The results showed an increase in participants’ understanding of chili cultivation techniques and a plant survival rate of 91.3–95.7 percent. The polybag system proved to be effective under flood-prone environmental conditions because it is easy to manage, movable, and does not require large land areas. In addition to providing economic benefits through potential savings in household food expenditures, this activity also raised community awareness of the importance of productive yard utilization. With continuous assistance and support from village institutions, this program has the potential to serve as a community-based adaptive agriculture model in flood-prone areas.